Determinants of outward FDI in developing countries - Chen, Jen Eem; Lee, Chin; Law, Siong Hook; Wan Ngah, Wan Azman Saini (2012)
This paper investigates the determinants of outward FDI in developing countries from home macroeconomics perspective. The study involves 7 developing countries and 3 emerging economies with time span covers from 1980 to 2010. The macroeconomic variables considered in this study are economic development, inward FDI, and trade openness. The findings reveal that economic development has a positive and significant relationship with outward FDI in the long-run. In the mean time, inward FDI is positively and significantly associated with outward FDI in the short-run.